HUBUNGAN KUALITAS TIDUR DENGAN TEKANAN DARAH DAN KEMAMPUAN KONSENTRASI BELAJAR MAHASISWA PROGRAM STUDI ILMU KEPERAWATAN UNIVERSITAS RIAU - Rika Diah Pitaloka; Gamya Tri Utami; Riri ' Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This study aims to determine the relationship between sleep quality with blood pressure and learning concentration ability of nursing student in University of Riau. This research was a descriptive correlation. Study was conducted in School of Nursing University of Riau Pekanbaru. Total sample were 100 people by using stratified random sampling technique with inclusion criteria. Measuring instruments used the Pitsburgh Sleep Quality Index questionnaire (PSQI) and concentration questionnaire that has been tested for validity and reliability. The analysis used univariate and bivariate with the Kolmogorov- Smirnov test and Chi-Square test. The results showed that there was no relationship between sleep quality and blood pressure (p= 0.418) on nursing students. There was a relationship between sleep quality and learning concentration ability (p= 0.002) on nursing students. The result of this study recommends nursing students to improve their sleep quality and their learning concentration ability Keywords: Blood pressure, learning concentration, PSQI, sleep quality